Chemical composition of smoke produced by open versus laparoscopic surgery for cholecystectomy. Issue 8 (August 2022) - Hsu, Francis Li-Tien; Ho, Te-Wei; Chang, Christopher; Wu, Jin-Ming; Lin, Ming-Tsan
Abstract: Background: Smoke produced by traditional open surgery (TOS) has long been considered hazardous to medical staff. Compared with TOS, minimally invasive surgery under carbon dioxide pneumoperitoneum is associated with a faster recovery and less wound pain. However, the impact of oxygen-deficient environment on the chemical contents of smoke has not been comprehensively assessed. Methods: This research evaluated the chemical composition and volatile organic compound (TVOC) level in smoke produced by open cholecystectomy (OC) versus laparoscopic cholecystectomy (LC) for gallbladder diseases. Smoke samples were collected and analyzed via gas chromatography–mass spectrometry. Chemical compounds were further grouped according to molecular weight and toxicity. Results: Compared with the OC, LC had significantly higher halocarbon and TVOC levels but lower cycloalkene and aldehyde levels. No halocarbons were isolated from OC specimens. When stratified based on molecular weight, LC had a bimodal pattern (i.e., high levels of small-sized [<60 Da] and large-sized [>120 Da] compounds). There was no difference in terms of toxicity types, incidence, and severity associated with detected compounds between two groups. Conclusion: LC is associated with a higher TVOC level and proportion of low- and high-molecular-weight organic compounds. Further strategies of evacuating these health hazards and preventing smoke leakage through trocars should be considered. Graphical abstract: Image 1